HUBUNGAN PERSEPSI TERHADAP LABEL PERINGATAN BAHAYA ROKOK PADA KEMASAN ROKOK DENGAN KEBIASAAN MEROKOK DI KELURAHAN NUSUKAN KECAMATAN BANJARSARI KOTA SURAKARTA - Diyono Diyono; Dewi Anggraeni (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
Background: This study was based on observations carried out because theresearcher amount or number of smokers in the community is still quite high. Thiscondition is very ironic because then our government through the healthdepartment conduct anti-smoking campaigns, but in fact has not been able todecrease the number of smokers significantly.Objective: to analyze the relationship between the perception of warning labelscigarette with smoking.Method: Research design correlation. The study population throughout theVillage community Nusukan Banjarsari District of Surakarta who have the habit ofsmoking, making approximately 100-150 residents. The sample size of 100respondents by using cluster random sampling technique sampling. Data wereanalyzed with Chi - Square with p: 0.005 SPSS 16 series.Results: (1) 90% pay attention to warning labels cigarette and only 10% who donot pay attention (2) Label the dangers of smoking in pictures more attention thatis 79% more than the writing that is 21% (3) label the dangers of cigarettes areperceived fear by 51% of the people and perceived unusual or fear as much as49% (4) the smoking habit lightweight category 6%, the moderate category was56% and having a heavy smoking habit of 38% of respondents.Conclusion: There was a significant correlation between the perception ofwarning labels cigarette with smoking (P = 0.000), with a moderate degree ofcorrelation (r = 0.391).Keyword: Perception, Hazard Warning Label Cigarette Smoking Habit